Perancangan dan Implementasi Sistem Administrasi Keuangan serta Katalog Produk Digital untuk Mendukung Ekspor UMKM Iluh Craft - Emella Kansa Sulthanah Gumay; Wisnu Yuwono (Faculty of Engineering, Universitas Semarang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) oriented toward export markets are required to possess well-structured financial administration systems and professional product promotion media. However, Iluh Craft MSME has faced challenges in the form of non-standardized financial recordkeeping and limited digital marketing tools, which potentially hinder operational efficiency and export readiness. This community service activity aimed to design and implement a financial administration system and a digital product catalog to enhance business management orderliness and marketing preparedness at Iluh Craft MSME. The implementation employed a descriptive–participatory approach through interviews, observations, documentation, system design, phased implementation, and joint evaluation with the partner. The results demonstrated a reduction in financial recording errors from approximately ±20% to less than 5%, an improvement in administrative time efficiency of up to ±40%, and fully organized document archiving reaching 100%. In addition, a bilingual digital product catalog was successfully developed and utilized as a promotional medium and sales reference. It can be concluded that the implementation of a structured financial administration system and a digital product catalog has a significant positive impact on operational efficiency, business professionalism, and the sustainable export readiness of Iluh Craft MSME.